The intra- and inter-population relatedness of bovine tuberculosis-infected and -uninfected African buffaloes (Syncerus caffer caffer) in the Kruger National Park - Van Schalkwyk, L.N. (Llewelyn Neil), 1952- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.